Antimicrobial effectiveness of Lysol® and quaternary ammonium during evaluation of three critical areas of the dental chair - Carvajal, Juan (2024)
Objective. Determine the antimicrobial efficacy of Lysol® and quaternary ammonium during the evaluation of three critical areas of the dental unit (control tray/buttons, dental chair back, and triple syringe handle). Methods. Through a cross-sectional comparative experimental study, a total of 8 dental chairs were analyzed: three were disinfected with Lysol®, three with quaternary ammonium, and two armchairs were selected as controls (positive and negative). All dental chairs were sampled twice a day: before use and at the end of use, for three days. Sampling was carried out at the Hemisferios University Clinics before and after the application of the disinfectant. The samples were transported in thioglycollate broth for analysis. 1:2 and 1:10 dilutions of each sample were plated on Plate Count Agar and incubated for 24 hours at 37°C. Subsequently, duplicate colony counts were performed, analyzing a total of 864 samples. Results. Lysol® and 5% quaternary ammonium showed equal antimicrobial effectiveness against the three areas analyzed (p>0.05). The area with the highest number of microorganisms was the tray (including control buttons). Conclusion. It was determined that both Lysol® and 5% quaternary ammonium are highly effective in eliminating microorganisms present on the critical surfaces of the dental unit. Furthermore, the tray, including the control buttons, was found to be the most contaminated area before treatment.